Mapping the in situ microspatial distribution of ice algal biomass through hyperspectral imaging of sea-ice cores - Cimoli, E; Lucieer, V; Meiners, KM; Chennu, A; Castrisios, K; Ryan, KG; Lund-Hansen, LC; Martin, A; Kennedy, F; Lucieer, A (Scientific Reports, 2020)
Ice-associated microalgae make a significant seasonal contribution to primary production and biogeochemical cycling in polar regions. However, the distribution of algal cells is driven by strong physicochemical gradients which lead to a degree of microspatial variability in the microbial biomass that is significant, but difficult to quantify. We address this methodological gap by employing a field-deployable hyperspectral scanning and photogrammetric approach to study sea-ice cores. The optical set-up facilitated unsupervised mapping of the vertical and horizontal distribution of phototrophic biomass in sea-ice cores at mm-scale resolution (using chlorophyll a [Chl a ] as proxy), and enabled the development of novel spectral indices to be tested against extracted Chl a (R 2 ≤ 0.84). The modelled bio-optical relationships were applied to hyperspectral imagery captured both in situ (using an under-ice sliding platform) and ex situ (on the extracted cores) to quantitatively map Chl a in mg m −2 at high-resolution (≤ 2.4mm). The optical quantification of Chl a on a per-pixel basis represents a step-change in characterising microspatial variation in the distribution of ice-associated algae. This study highlights the need to increase the resolution at which we monitor under-ice biophysical systems, and the emerging capability of hyperspectral imaging technologies to deliver on this research goal.